Editorial: BRICS in an Evolving World Order - M. Yu. Apanovich; Fulufhelo Netswera (Vestnik MGIMO-Universiteta)
The editorial explores the evolution of the BRICS community, overviewing the articles included in the special issue. The authors emphasize various facets of ongoing and evolving cooperation, delineating how BRICS nations engage with climate change, development assistance and collaboration, global governance reform, and the progressive advancement of the New Development Bank (NDB).